The Criminalization of Socio-Environmental Struggles in Puerto Rico - Atiles-Osoria, José M. (2014)
Throughout the twentieth century and the outset of the twenty-first, Puerto Rico’s sociopolitical and pro-independence struggles from US colonial rule have been influenced by the emergence of mobilizations for environmental justice. This article suggests that our understanding of both environmental and anticolonial mobilizations can be broadened by considering Puerto Rico’s sociopolitical and colonial reality, as well as emphasizing the criminalization processes that take place as an institutional reaction to social mobilization. The structure of the article follows a threefold analysis. In the first part, I describe the historical basis of Puerto Rico’s colonial situation, including its environmental impact, outlining the intertwined nature of these two processes. The second part outlines the mechanisms of repression and criminalization developed by the US and Puerto Rican governments. Finally, part three analyses the Puerto Rican environmental conflicts between 1999 and 2012, as well as how pro-environmental civil disobedience became a criminal offence.